نظم القرآن من حيث المنهج لتفسير القرآن الكريم: دراسة تحليلية لمبادئه (Coherence in the Qur’an as a Methodology of Tafsir: An Analytical Study of Its Principles) - خان, إسرار أحمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص مما لا شكّ فيه أنّ اختلافا شاسعا وخلافا شديدا قد وقع بين العلماء والفقهاء والمفسرين في تفهيم معنى القرآن الحكيم، فتفرق المسلمون في العصر الراهن في فهم الآيات القرآنية وامتثالهم بها. فيمكن القول بأن منهج تفسير القرآن الذي يؤدي إلى افتراق الأمة ليس هو المنهج المناسب. ويبدو أنّ القرآن يُفسّر لأحد الهدفين، لاستنباط حكمٍ في مسألة ما أو لإثبات عقيدة خاصة. والمنهج المناسب هو المنهج الذي يهدي الناس بصورة عامة والمسلمين بصورة خاصة إلى الوحدة. فجاء بعض المفسرين بمنهجٍ لتفسير القرآن الكريم يقال له: "نظم القرآن" الذي يطلب من المفسر أن يتبع بعض الأصول والمبادي التي يظهر باستخدامها في تدبر القرآن الترابط والانسجام والاتحاد بين كل ما جاء القرآن به. ومن المفسرين البارزين الذين فسروا القرآن الكريم على أساس النظم هم الحرالّي (ت637هـ) والبقاعي (ت885هـ)، والفراهي (ت1930م)، والإصلاحي (ت1997م). في هذا المنهج عشرة مبادئ تُستخدم في تفسير القرآن. وهذا البحث يتناول دراسة تحليلية لتلك المبادئ العشرة. الكلمات المفتاحية: نظم القرآن، منهج التفسير، افتراق الأمة، الفراهي، الإصلاحي. Abstract Undoubtedly, very serious differences have occurred among Muslim scholars, jurists, and commentators in explaining meaning of the Qur’an. It has led the Muslims in general to disunity as to the understanding of the Qur’anic verses and their implementation in life. It may then be said that methodology of the Qur’anic interpretation which causes dissension among Muslims is not appropriate methodology. Generally, the Qur’an is interpreted either to derive a legal ruling on a given issue or prove sanctity of a particular belief whatsoever. The appropriate methodology of Qur’anic interpretation is the one which brings unity among Muslims in particular and the humanity in general. Towards that end some Muslim scholars developed a new methodology of Qur’anic interpretation known as “Coherence”, which requires of Mufassirun to follow certain principles so as to show that all the components of the Qur’an are interconnected, cohesive, and coherent. The most prominent scholars, who applied “Coherence” methodology in Qur’anic interpretation, are al-Harālliyy (637 A.H.), al-Biqāai (885 A.H.), al-Farāhi (1930 C.E.), and Islahi (1997 C.E.). The principles of “Coherence” are ten. This paper is devoted to deliberate over these ten principles. Keywords: Coherence in the Qur’an, Methodology of Qur’anic Interpretation, Muslims’ Disunity, Al-Farāhi, Islahi.